2013
DOI: 10.1371/journal.pone.0059336
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Effects in Relation to Helper Presence in the Cooperatively Breeding Sociable Weaver

Abstract: In egg laying species, breeding females may adjust the allocation of nutrients or other substances into eggs in order to maximise offspring or maternal fitness. Cooperatively breeding species offer a particularly interesting context in which to study maternal allocation because helpers create predictably improved conditions during offspring development. Some recent studies on cooperative species showed that females assisted by helpers produced smaller eggs, as the additional food brought by the helpers appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
58
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 87 publications
3
58
5
Order By: Relevance
“…For example, in studies of cooperative meerkats, Suricata suricatta (Russell, Brotherton, McIlrath, Sharpe, & Clutton-Brock, 2003), increasing helper number indirectly increases pup mass at burrow emergence, as helpers boost maternal weight at conception, and heavier mothers produce heavier pups. By contrast, in fish species (Taborsky, Skubic, & Bruintjes, 2007) and a range of birds (Canestrari, Marcos, & Baglione, 2011;Paquet, Covas, Chastel, Parenteau, & Doutrelant, 2013;Russell, Langmore, et al, 2007;Santos & Macedo, 2011), studies have generally reported a reduction in prebirth investment with increasing group size (for an exception see Koenig, Walters, & Haydock, 2009), without a corresponding change in the number of offspring produced.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in studies of cooperative meerkats, Suricata suricatta (Russell, Brotherton, McIlrath, Sharpe, & Clutton-Brock, 2003), increasing helper number indirectly increases pup mass at burrow emergence, as helpers boost maternal weight at conception, and heavier mothers produce heavier pups. By contrast, in fish species (Taborsky, Skubic, & Bruintjes, 2007) and a range of birds (Canestrari, Marcos, & Baglione, 2011;Paquet, Covas, Chastel, Parenteau, & Doutrelant, 2013;Russell, Langmore, et al, 2007;Santos & Macedo, 2011), studies have generally reported a reduction in prebirth investment with increasing group size (for an exception see Koenig, Walters, & Haydock, 2009), without a corresponding change in the number of offspring produced.…”
mentioning
confidence: 98%
“…more helpers) should invest more to exploit current conditions, or save resources to increase their future survival probability. To this end, we explore two possible effects of increased maternal investment on outcomes for offspring: a 'head start' relationship under which greater prebirth investment leads to lower postbirth investment from the entire care group (Paquet et al, 2013;Russell, Langmore, et al, 2007), and a 'silver spoon' relationship under which prebirth investment has long-term effects on offspring phenotype (Eising, Müller, & Groothuis, 2006;Strasser & Schwabl, 2004), but may lead to greater demands during rearing, for example if larger offspring require more food (Clutton-Brock, Albon, & Guinness, 1985;Klaassen & Bech, 1992). This approach contrasts with previous theoretical work on parental care, which has focused on either postbirth investment in isolation (Houston & Davies, 1985;McNamara, Gasson, & Houston, 1999) or maternal control of offspring number rather than offspring 'quality' (Savage, Russell, & Johnstone, 2013a, 2013b.…”
mentioning
confidence: 99%
“…2007; Taborsky, Skubic & Bruintjes 2007; Canestrari, Marcos & Baglione 2011; Santos & Macedo 2011; Paquet et al . 2013). Hence, in these species, a stronger effect of helpers might be expected on female survival compared to male survival.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sociable weaver females lay lighter eggs when assisted by helpers (Paquet et al . 2013). Therefore, we predict a greater positive effect of the presence of helpers on female than on male survival probability.…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative breeders are usually long-lived species (Arnold & Owens, 1998;Covas & Griesser, 2007) and females with good future reproductive prospects are expected to decrease their investment in eggs with an increasing number of helpers in order to maximize their lifetime reproductive success (Russell & Lummaa, 2009). Indeed, recent results have shown that females may invest less by producing smaller eggs when they have helpers, since the additional food brought by the helpers will compensate for this difference in egg size (Canestrari, Marcos, & Baglione, 2011;Paquet, Covas, Chastel, Parenteau, & Doutrelant, 2013;Russell, Langmore, Cockburn, Astheimer, & Kilner, 2007;Santos & Macedo, 2011). Additionally, in the presence of helpers, sociable weaver, Philetairus socius, females have been found to deposit less steroid hormones in eggs , which are potentially immunosuppressive (see Groothuis, Muller, von Engelhardt, Carere, & Eising, 2005 for a review).…”
mentioning
confidence: 99%